Nitric Oxide in the Offensive Strategy of Fungal and Oomycete Plant Pathogens - Arasimowicz-Jelonek, Magdalena (Front Plant Sci, 2016)
In the course of evolutionary changes pathogens have developed many invasion strategies, to which the host organisms responded with a broad range of defense reactions involving endogenous signaling molecules, such as nitric oxide (NO). There is evidence that pathogenic microorganisms, including two most important groups of eukaryotic plant pathogens, also acquired the ability to synthesize NO via non-unequivocally defined oxidative and/or reductive routes. Although the both kingdoms Chromista and Fungi are remarkably diverse, the experimental data clearly indicate that pathogen-derived NO is an important regulatory molecule controlling not only developmental processes, but also pathogen virulence and its survival in the host. An active control of mitigation or aggravation of nitrosative stress within host cells seems to be a key determinant for the successful invasion of plant pathogens representing different lifestyles and an effective mode of dispersion in various environmental niches.